How does harvest size vary with hunting season length?. Issue 3 (1st June 2014) - Sunde, Peter; Asferg, Tommy
Abstract : Manipulating hunting season length is often used as a population management tool but the effects of these changes on total harvest have rarely been studied. We modelled relative changes in national annual bag size as a function of relative change in hunting season length in 63 cases involving 28 species in Denmark (1957–2007). The duration of the hunting season, initially lasting 30–365 days, was modified to 39–204% of the former length. The undifferentiated effect of season length change on bag size change (all 63 cases) was not statistically significant (b = 0.16, 95%CI: ‐0.04–0.36), with a 10% (95%CI: ‐3–22%) predicted decrease in bag size upon a 50% reduction of season length. However, the functional relationship between the relative change in bag size and the change in season length differed between sedentary and non‐sedentary species and interacted with the motivation behind changing season length (population management/ethical/other). In non‐sedentary species, changes in bag size correlated positively with changes in season length (overall response: b = 0.54, 95%CI: 0.14–0.95): reducing the hunting season to 50% of its initial length would on average result in a 31% reduction (95% CI: 9–48%) of total bag size. This overall effect interacted with the motivation for season length changes, being strongest for 'other reasons' (mainly harmonization of hunting periods for related species) but was absent when seasons were changed for reasons of 'population management'. In sedentary species, changes in season length had no effect on bag size. Our results suggest that manipulating hunting seasons of duration ≥ 1 month by less than 50% is generally inefficient as a means of predictably changing harvest rates. This may be because recreational hunters either invest a fixed effort or aim for a specific yield within a given season, neither strategy being affected by changes in hunting seasons.